Pembelajaran Blending Asynchronous-Synchronous Learning Berbasis Relevan terhadap Hasil Belajar Koqnitif Peserta Didik Sekolah Dasar pada Masa Pandemi - Lidia Susanti; Rira Estherina (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2022)
Research on blending relevance based asynchronous and synchronous learning across the cognitive result of 5th grade elementary school students. The aim is to determine the impact of online learning on cognitive students. In this research, the control class and the experimental class received the same learning media, asynchronous learning using the Google Classroom application so that students could send materials, collect assignments and communicate indirectly with the teacher. Meanwhile, synchronous learning uses a zoom application, where students can interact and communicate with teachers and friends directly. The control class did not use relevant-based learning with a total of 24 children and the experimental class, which used relevant-based learning, amounted to 44 children. The results showed that the average pretest for the control class was 54.38 and the experimental class was 55.94. On the other hand, the average posttest for the control class was 63.54 and the experimental class was 83.50. These results show a significant difference, then continued with statistical tests to the correlation test stage and obtained significant results of 0.743 and 0.000 sig. The contribution of relevant-based learning is 55.1% to students' cognitive learning outcomes.